Articulation error of children with adenoid hypertrophy - Tae-Hoon Eom; Eun-Sil Jang; Young-Hoon Kim; Seung-Yun Chung; In-Goo Lee (Korean Pediatric Society, 2014)
PurposeAdenoid hypertrophy is a physical alteration that may affect speech, and a speech disorder can have other negative effects on a child's life. Airway obstruction leads to constricted oral breathing and causes postural alterations of several oro-facial structures, including the mouth, tongue, and hyoid bone. The postural modifications may affect several aspects of speech production.MethodsIn this study, we compared articulation errors in 19 children with adenoid hypertrophy (subject group) to those of 33 children with functional articulation disorders independent of anatomical problems (control group).ResultsThe mean age of the subject group was significantly higher (P=0.016). Substitution was more frequent in the subject group (P=0.003; odds ratio [OR], 1.80; 95% confidence interval [CI], 1.23-2.62), while omission was less frequent (P<0.001; OR, 0.43; 95% CI, 0.27-0.67). Articulation errors were significantly less frequent in the palatal affricative in the subject group (P=0.047; OR, 0.25; 95% CI, 0.07-0.92). The number of articulation errors in other consonants was not different between the two groups. Nasalization and aspiration were significantly more frequent in the subject group (P=0.007 and 0.014; OR, 14.77 and 0.014; 95% CI, [1.62-135.04] and NA, respectively). Otherwise, there were no differences between the two groups.ConclusionWe identified the characteristics of articulation errors in children with adenoid hypertrophy, but our data did not show the relationship between adenoid hypertrophy and oral motor function that has been observed in previous studies. The association between adenoid hypertrophy and oral motor function remains doubtful.